ANALYSIS OF FACTORS AFFECTING THE IMPORT OF DAIRY MILK (CASE STUDY: THE IMPORT OF DAIRY MILK IN INDONESIA) - Kustopo Budiraharjo; Budi Raharjo; Solikhin Solikhin (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
The supply of fresh dairy milk in the country (SSDN) has not been able to meet the needs of domestic dairy milk consumption so that the fulfillment of dairy milk consumption needs is also done byimporting dairy milk. This study aims to analyze the factors that influence milk imports in Indonesia.The research method uses quantitative analysis techniques, namely multiple linear regression. This research was conducted in Indonesia using secondary data from 2006-2016 obtained at the Central Statistics Agency and the Ministry of Agriculture and other literature related to research. Research variables include exchange rates, GDP per capita, milk exports, and milk production. The results showed that variables GDP per capita, milk exports, and milk production have positive influence. Meanwhile, exchange rate has negative influence for milk imports.